2012
DOI: 10.1590/s0037-86822012000200014
|View full text |Cite
|
Sign up to set email alerts
|

Biological behavior of Trypanosoma cruzi stocks obtained from the state of Amazonas, Western Brazilian Amazon, in mice

Abstract: Introduction:The biological diversity of circulating Trypanosoma cruzi stocks in the Amazon region most likely plays an important role in the peculiar clinic-epidemiological features of Chagas disease in this area. Methods: Seven stocks of T. cruzi were recently isolated in the State of Amazonas, Brazil, from humans, wild mammals, and triatomines. They belonged to the TcI and Z3 genotypes and were biologically characterized in Swiss mice. Parasitological and histopathological parameters were determined. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Acquiring knowledge about the biological properties of the TcIV lineage, which certainly plays an important role in the Chagas disease pathogenesis and response to the specific chemotherapy in the Amazon region, represents a challenge for future research. Our preliminary results indicate that Amazonian T. cruzi isolates promote scarce parasitemia and low virulence and pathogenicity in mice in comparison to TcII strains [54], [55]. At least in Brazil, TcII and rarely TcI, appear to be exclusively responsible for the tissue lesions in chronic Chagas disease [19], [23], [56], [57].…”
Section: Discussionmentioning
confidence: 72%
“…Acquiring knowledge about the biological properties of the TcIV lineage, which certainly plays an important role in the Chagas disease pathogenesis and response to the specific chemotherapy in the Amazon region, represents a challenge for future research. Our preliminary results indicate that Amazonian T. cruzi isolates promote scarce parasitemia and low virulence and pathogenicity in mice in comparison to TcII strains [54], [55]. At least in Brazil, TcII and rarely TcI, appear to be exclusively responsible for the tissue lesions in chronic Chagas disease [19], [23], [56], [57].…”
Section: Discussionmentioning
confidence: 72%
“…TcIV predominates among orally transmitted acute human cases (34) , and TcI predominates among the isolated and chronic cases (35) (38) , suggesting their association with different transmission profiles. The T. cruzi isolates showed variable behavior in experimental infections in mice, promoting low parasitemia, virulence and pathogenicity, which is compatible with the low parasitemia and morbidity profi le of CD in humans and with the poor performance of diagnostic methods in the region (43) . In mice, the frequency of resistance to benznidazole among the TcIV isolates was signifi cantly higher than in the TcI isolates (35) .…”
Section: Chagas Disease In the State Of Amazonasmentioning
confidence: 91%
“…Despite the high prevalence, several clinical studies have reported that the acute phase is marked with high morbidity, including some fatal cases of dilated cardiomyopathy 6,19 . It has been reported that Chagas disease in the Middle Negro river has a clinical profile of low morbidity and mortality in the chronic phase 12 . The biological diversity of circulating T. cruzi has an important role in the clinical, immunological and epidemiological features of Chagas disease in the Amazon basin 12,13,18 .…”
Section: Seroepidemiological and Immunological Relationshipsmentioning
confidence: 99%
“…It has been reported that Chagas disease in the Middle Negro river has a clinical profile of low morbidity and mortality in the chronic phase 12 . The biological diversity of circulating T. cruzi has an important role in the clinical, immunological and epidemiological features of Chagas disease in the Amazon basin 12,13,18 . It has been suggested that the low parasite load and low levels of serum IgG anti-T. cruzi might reflect the discrete typing units of T. cruzi in this case TcI prevalent in the Brazilian Amazon, instead of the TcII, TcV and TcVI genotypes predominant in the domestic transmission cycle of the South Cone in the South America, where chagasic patients are characterised by higher parasitaemia, virulence and pathogenicity 12 .…”
Section: Seroepidemiological and Immunological Relationshipsmentioning
confidence: 99%